Abu al-‘Atahiyyah's Perspective on Religious Moderation in Arabic Poetry - Latif, Abdul; Usman Imam, Luqman bin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
A.Teeuw stated that human being have at least four paths to understanding reality and truth: religion, science, philosophy, and art. Literature is distinct from three other truths as art. Literature can go beyond dogma, science, and philosophy. Poets can continue to be creative and imaginative, offering unrestricted thinking as long as their language moves the reader's emotions in accordance with truth fiction. This article attempted moderation with the four indicators of religious moderation developed by the Ministry of Religious Affairs of the Republic of Indonesia which based on Abu al-'Atahiyyah perspective about religious moderation which were extracted from his poetry anthology with the note-taking technique. Afterwards, it was analyzed with a pragmatic approach in literary studies. The findings of this study indicated that Abu al-‘Atahiyyah also discussed the religious moderation in terms of tolerance, nonviolence, and accommodating local culture. As a result, this article demonstrated that the concepts of truth can also be found in literary works.